2015
DOI: 10.1377/hlthaff.2015.0272
|View full text |Cite
|
Sign up to set email alerts
|

High-Cost Patients Had Substantial Rates Of Leaving Medicare Advantage And Joining Traditional Medicare

Abstract: Medicare Advantage payment regulations include risk-adjusted capitated reimbursement, which was implemented to discourage favorable risk selection and encourage the retention of members who incur high costs. However, the extent to which risk-adjusted capitation has succeeded is not clear, especially for members using high-cost services not previously considered in assessments of risk selection. We examined the rates at which participants who used three high-cost services switched between Medicare Advantage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 17 publications
6
95
1
Order By: Relevance
“…Our findings extend previous work demonstrating 15 that the persons with intensive care needs, including those with prior hospitalizations and long-term and short nursing home stays, are more likely to exit MA plans, compared with those who do not use these services. Further study of the reasons for disenrollment is urgently needed, because the benefits of managed care may be attenuated if patients exit their plans once they have complex medical needs.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings extend previous work demonstrating 15 that the persons with intensive care needs, including those with prior hospitalizations and long-term and short nursing home stays, are more likely to exit MA plans, compared with those who do not use these services. Further study of the reasons for disenrollment is urgently needed, because the benefits of managed care may be attenuated if patients exit their plans once they have complex medical needs.…”
Section: Discussionsupporting
confidence: 86%
“…Others studies have found that there was no reduction in risk selection (Brown, Duggan, Kuziemko, & Woolston, 2014; Morrisey, Kilgore, Becker, Smith, & Delzell, 2013). Importantly, there are some data that switching from MA plans became concentrated among high-cost beneficiaries (Morrisey et al, 2013; Rahman et al, 2015)…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of how the quality of SNF care received by MA beneficiaries may differ from that received by FFS patients. 17 It is possible to study these issues using the mandatory patient assessments that each SNF submits to CMS on all entering beneficiaries, including MA patients.…”
mentioning
confidence: 99%